United Learning (A) - Diermeier, Daniel; Hughes, Gregory L. (London : SAGE Publications Ltd, 2017)
United Learning is a family-owned leader in the K-12 supplementary teaching material market. In January 2001, United Learning realized that sales for one of its flagship products, a drug and prevention program, were rapidly deteriorating because the program was not mentioned on a recently released U.S. Department of Education list of recommended products. United Learning must decide on which action to take: regain sales or focus on its other educational products--which are also threatened by changes in the regulatory environment.
Originally published: Diermeier, D., & Hughes, G. L. (2004). United Learning (A). 5-403-752(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; United Learning (Charity) -- Case studies; Teaching -- Aids and devices -- Case studies; Drug abuse -- Study and teaching -- Case studies; Nonprofit organizations -- England -- Case studies